The dark side of empowering leadership: Hindrance stressors and moral disengagement as pathways to unethical pro-organizational behaviour - Fajri, Annisa; Suharnomo, Suharnomo; Djastuti, Indi (Jurnal Siasat Bisnis, 2026)
Purpose – This study examines the conditional association between empowering leadership and unethical pro-organizational behaviour (UPB). Drawing on Social Cognitive Theory, it investigates whether moral disengagement statistically accounts for this association and whether hindrance stressors condition the association between empowering leadership and moral disengagement.Design/methodology/approach – Data were collected through a cross-sectional online survey of 500 employees working in Indonesian digital start-ups. The proposed first-stage moderated mediation model was tested using PROCESS Model 7 for SPSS with 5,000 bootstrap resamples and 95% bootstrap confidence intervals.Findings – Empowering leadership was positively associated with moral disengagement, and this association became stronger as hindrance stressors increased. Moral disengagement was positively associated with UPB, while the direct association between empowering leadership and UPB remained statistically significant. The conditional indirect association was positive at all examined levels of hindrance stressors and became progressively stronger as those stressors increased. The positive index of moderated mediation supported an amplification rather than a reversal pattern (index = 0.0897, 95% BootCI [0.0674, 0.1124]).Research limitations/implications – The cross-sectional, single-source design does not establish temporal or causal ordering and may be affected by common method bias. Convenience and social-media-based recruitment may also introduce sampling and self-selection biases, limiting representativeness and generalizability.Practical implications – Organizations should accompany employee empowerment with clear ethical boundaries, adequate structural support, and efforts to reduce obstructive workplace demands. These recommendations should be interpreted as precautionary considerations rather than causally established interventions.Originality/value – The study provides a contextual replication and boundary-pattern extension of prior research. It refines understanding of a boundary condition by finding an amplification pattern in a non-Western digital start-up setting rather than proposing a new mechanism.